The Influence of Oral Hygiene Using NaCl 0.9% and Chlorhexidine on Ventilator Associated Pneumonia (VAP) in the ICU of Jakarta Hospital - Noviana Haryanti; Irna Nursanti; Diana Irawati (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2024)
Background: VAP is a problem found in patients who are on a ventilator, the VAP has not been considered by nursing staff when providing nursing care processes, starting from when reviewing patients, conducting interventions and evaluating patients. Prevention is done from the beginning of nursing care, one of which is oral hygiene. Objectives: The purpose of this study was to examine the effect of oral hygiene using a combination of 0.9% Natrium Chloride (NaCl) and Chlorhexidine (CHG) in patients who were on a ventilator. Methods: The design of this study was a quasi experiment with a pretest-post test with a control group design. The sampling technique used the Federer formula with a sample of 18 respondents with 9 respondents per group. Statistical analysis used in this research is univariate characteristic test, bivariate test with paired t-test and for multivariate using simple linear regression test for confounding. Results: Of the research conducted showed that there was no significant effect in group A before and after the intervention with a p-value (0.403) and the average increased slightly, while group B before and after the intervention had a p-value (0.512) with a decreasing average. The multivariate test found that age confounding had an effect on VAP with a p-value (0.024) while gender confounding had no effect on VAP with a p-value (0.277). Conclusion: In this study, oral hygiene using a combination of 0.9% NaCl and CHG was effective against VAP.